1984
DOI: 10.1046/j.1468-2982.1984.0401009.x
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Pupillary and Heart Sympathergic Asymmetries in Cluster Headache

Abstract: Ten cluster headache patients and 10 healthy controls were subjected to electrocardiographic and pupillometric procedures in a search for cardiac and pupillary sympathergic asymmetry. Sympathergic stimulation was provoked by hyperventilation and by instilling tyramine into both eyes. In the control group, hyperventilation changed neither the T-wave form and polarity nor the QTc. Tyramine provoked an equal mydriasis on the two sides. In cluster headache sufferers, hyperventilation produced changes in the T-wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…In fact, pretreatment with clonidine augmented the degree of anisocoria induced by tyramine instillation, increasing the mydriatic response only on the pain-free side in CH patients. This finding has been corroborated by Salvesen et al (15) and by Boccuni et al (16). The latter authors have also demonstrated that hyperventilation-provoked sympathergic stimulation produces electrocardiographic changes consistent with asynchronous repolarization due to impaired central sympathetic activity.…”
Section: Discussionsupporting
confidence: 61%
“…In fact, pretreatment with clonidine augmented the degree of anisocoria induced by tyramine instillation, increasing the mydriatic response only on the pain-free side in CH patients. This finding has been corroborated by Salvesen et al (15) and by Boccuni et al (16). The latter authors have also demonstrated that hyperventilation-provoked sympathergic stimulation produces electrocardiographic changes consistent with asynchronous repolarization due to impaired central sympathetic activity.…”
Section: Discussionsupporting
confidence: 61%
“…1,2 Many researches have been carried out to understand the actual relationship between painful crises and autonomic features, which tend to play a prominent role in headache pathophysiology. 8,9,10,11,12 Some evidence, however, points out a more complex autonomic defect, since most of these symptoms involve both a sympathetic and a parasympathetic activation, such as salivation, nasal secretion and tea ring . An asymmetric sympathetic regulation of the pupillary reactivity, nasal glands secretion, and forehead sweating support the idea of defective sympathetic function on the symptomatic side.…”
Section: Introductionmentioning
confidence: 99%
“…Does this also affect autonomic control of the heart, which contains distinct right and left innervations? Changes in the T‐wave configuration as well as an increase in QT c which could be caused by differential sympathetic activity in the right and left stellate ganglion would seem to confirm this . The proposed mechanism involves differences in the length of action potentials in different parts of the heart leading to asynchronous repolarization producing the increased QT c .…”
Section: Resultsmentioning
confidence: 84%